2018
DOI: 10.1016/j.clinbiomech.2018.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Local bone quality measurements correlates with maximum screw torque at the femoral diaphysis

Abstract: Reference Point Indentation can provide localized measurements of bone quality that may better inform surgeons of the competence of the bone-implant interface and improve effectiveness of fixation strategies particularly in patients with compromised bone quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…In this study, the screws were inserted in identical synthetic cortical bone reproduction, which can be considered as a limit of the investigation, although it avoided results bias. Among the factors that were taken into consideration during this study, the influence of the screw diameter was significant, in accordance with previous findings [9]. The shape of the screw influenced the insertion torque as well, as shown in Fig.…”
Section: Quantitysupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the screws were inserted in identical synthetic cortical bone reproduction, which can be considered as a limit of the investigation, although it avoided results bias. Among the factors that were taken into consideration during this study, the influence of the screw diameter was significant, in accordance with previous findings [9]. The shape of the screw influenced the insertion torque as well, as shown in Fig.…”
Section: Quantitysupporting
confidence: 90%
“…Low insertional torque can cause poor compressive force between the plate and the bone [8]. On the other hand, excessive insertional torque can lead to the stripping of the screw, affecting its primary stability [9][10][11]. High insertional torque is also related to a greater inflammatory response of the tissue near the implant, which can lead to the failure of the implant as well [12].…”
Section: Introductionmentioning
confidence: 99%
“…BioDent was also capable of monitoring the effects of in vitro aminoguanidine and pyridoxamine incubation on ex vivo bone tissue mechanical behavior 52 . In another application, IDI was used to predict maximum screw torque in fracture fixation 53 .…”
Section: Biodent Studiesmentioning
confidence: 99%
“…The important factor in the success of fixation is the used implantation technique and the quality of the osseous tissue of the bone [34]. McAndrew et al [11] describe that the bone mineral density (BMD) is a widely used standard in the measurement of bone mass and can be used to identifying the bone strength. They also reported that the strength of the bone-screw interface is dependent on the local bone quality.…”
Section: Bone Qualitymentioning
confidence: 99%
“…The use of screw advantages are it superior torsional stability, minimally invasive insertion and limited disruption of femoral head blood supply. It is also beneficial to surgeon as the use of screw will limit blood loss, operating time, and damage to the soft tissue that will promote better healing to the patient [10] The fracture fixation achievement depend on the screw-bone interface stability [11]. The stability of the fixation will support the fracture to increase it vascularity and tissue differentiation, accelerate the fracture union and promote early callus formation [12].…”
Section: Introductionmentioning
confidence: 99%